CONTRIBUTO NA COMUNIDADE DO RISCO : COLERA NO BAIRRO 1º DE MAIO SOALPO EM CHIMOIO - ESTUDO DE CASO (REMUNOM, 2023)
Abstract This articule aims to understand the level of knowledge about cholera and risk treatment in the 1o de Maio neighborhood. For this I bring some observations, to achieve the objectives resorted to the qualitative methodology due to the fact of descriptive predominance , the information brought is rich as it needs to ring results by experience And interview. With the analysis of the results , it is concluded that cholera arises due to lack of care in the community and it affects disadvantaged people. And great care is given by conditioned people. Thus , community resistance to individual risk ends up with cholera , which can affect a large number of individuals and , if poorly prevented can end life.Keywords : cholera, contribution , risk , 1 st of may